Comparison of a Point-of-Care Assay and a High-Complexity Assay for Detection of SARS-CoV-2 RNA. (6th August 2020) - Stevens, Bryan; Hogan, Catherine A; Sahoo, Malaya K; Huang, ChunHong; Garamani, Natasha; Zehnder, James; Kurzer, Jason; Pinsky, Benjamin A
Abstract: Background: Numerous nucleic acid amplification assays utilizing different target genes of the SARS-CoV-2 genome have received emergency use authorization (EUA) by the United States Food and Drug Administration (FDA). Limited data are available comparing the test performance characteristics of these assays. Methods: A diagnostic comparison study was performed to evaluate the performance of the Cepheid Xpert Xpress SARS-CoV-2 assay compared to the Hologic Panther Fusion SARS-CoV-2 assay using clinical nasopharyngeal specimens. Agreement between the two assays was assessed by overall, positive, and negative percent agreement and Cohen's kappa coefficient. Results: A total of 104 (54 positive and 50 negative) clinical nasopharyngeal samples were tested by both assays. Using the Panther Fusion as a reference standard, the Xpert demonstrated an overall agreement of 99.0% [95% confidence interval (CI): 94.8–100], positive percent agreement of 98.1% (95% CI: 90.1–100), and a negative percent agreement of 100% (95% CI: 94.2–100). The kappa coefficient was 0.98 (95% CI: 0.94–1.0). One sample positive by the Panther Fusion with a cycle threshold (Ct) of 38.6 was found to be reproducibly negative by the Xpert assay. Conclusions: The Cepheid Xpert Xpress SARS-CoV-2 assay provides test performance comparable to the Hologic Panther Fusion SARS-CoV-2 assay while offering laboratories rapid, on-demand testing capacity.